Modelo de avaliação de boas práticas de dados geográficos aplicados ao Centro Internacional de Hidroinformática - Ferreira, Ana Caroline (2019)
Brazil is a country with one of the largest territories in the world, and is able to produce map it, with efficiency is critical. To make this possible, it is necessary to organize the process of collecting and distributing geographic data. The World Wide Web Consortium (W3C) and Open Geospatial Consortium (OGC) companies jointly defined a list of spatial data best practices to provide reusable infrastructures that can be easily used by search engines. No national scope was specified by presidential decree 6,666 to the National Spatial Data Infrastructure (INDE). To help the organization process is suggested in this research in the Spatial Data Infrastructure Assessment Model, this model combines some of the specifications of Brazil's National Spatial Data Infrastructure (INDE) and the W3C and OGC Web Spatial Data Best Practices. . The adopted model was applied to 21 Geographic Information Systems (GIS), belonging to the Local Spatial Data Infrastructure of the International Center for Hydroinformatics (CIH). The displayed results, which can be used using the controlled model as a result, generate a 2-point indication that they change within an English Spatial Data Infrastructure (SDI), which consists of centralizing services and organizing the data. GIS for centralization, in order to promote better distribution and use them by other researchers.